2022
DOI: 10.3389/fnagi.2022.936027
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different types of Tai Chi exercises on motor function in patients with Parkinson's disease: A network meta-analysis

Abstract: BackgroundTai Chi can show improvement in balance and motor ability of elderly patients with PD. However, there were few reports on differences in outcomes associated with different types of Tai Chi on improving exercise capacity in elderly patients with PD. We compared the improvement of motor function in Parkinson's patients with different types of Tai Chi, for finding an optimal intervention.MethodsThe following databases were searched from the beginning of the establishment of each database to 10 January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Figure 10 showed the relationship between the four types of Tai Chi in a network diagram, two RCTs comparing 24-form with the control group, four RCTs comparing Sun style with the control group, five RCTs comparing Yang style with the control group, and one RCT comparing TCEP with the control group. Since there were no loops in the network diagram, we directly used the consistency model to compare these interventions [ 40 ]. The interval plot (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 10 showed the relationship between the four types of Tai Chi in a network diagram, two RCTs comparing 24-form with the control group, four RCTs comparing Sun style with the control group, five RCTs comparing Yang style with the control group, and one RCT comparing TCEP with the control group. Since there were no loops in the network diagram, we directly used the consistency model to compare these interventions [ 40 ]. The interval plot (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Mind-Body Therapies (MBTs), such as Tai Chi Chuan, show potential in reducing depressive symptoms, psychological distress (Kuang et al, 2024;Recchia et al, 2024), physical function like blood pressure reduction (Yin et al, 2023), improving motor function in patients with Parkinson's disease (Lei et al, 2022) improving cognitive function (Chen et al, 2024;Sungkarat et al, 2018), effects on cognition at the behavioral and neuroelectric levels (Lei et al, 2022), improve individuals' working memory capacity, and then improve their emotion regulation ability (Wang et al, 2023) and treating insomnia and offering a diverse range of psychological and physiological bene ts (Jimenez et (Abbott & Lavretsky, 2013;Jimenez et al, 2012). These studies emphasise the interrelated aspects of the body, mind, and behaviour (Y.…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture, a popular complementary and alternative medicine approach, is recommended as therapy for PD patients based on level B evidence (32,33). Recent meta-analyses have shown that acupuncture in conjunction with conventional medication exhibits a notable positive impact on movement function in PD patients (34,35). Animal studies corroborate these ndings, suggesting acupuncture's potential in alleviating PD symptoms (36,37).…”
Section: Introductionmentioning
confidence: 99%